Süleymaniye Cami ve imareti inşaatı, 1550-1557 - Barkan, Ömer Lütfi, 1902-1979. (Ankara Ankara)
2 cilt (1. c. xv, 393 sayfa, [1] katlı plan, [3] katlı grafik, [4] katlı tablo ; 2. c. vii, 293, [8] sayfa )